MATERIALISTIS DALAM NASKAH DRAMA NYONYA-NYONYA KARYA WISRAN HADI: KAJIAN SOSIOLOGI SASTRA - Muhammad Bunga Ashab; Andria Catri Tamsin; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2012)
This research is to describe: (a) the materialism of “Nyonya” in the script of play Nyonya-Nyonya by Wisran Hadi and (b) the impact of the materialism of “Nyonya” in the script of Nyonya-Nyonya by Wisran Hadi. This research is a qualitative research applying qualitative descriptive method. This research Data is a form of materialism and the impact of materialism of “Nyonya” in the script of play Nyonya-Nyonya by Wisran Hadi. The sources in this research are five scripts of drama: the winner of Competition Drama Script “Dewan Kesenian Jakarta”, 2003. The technic of gathering data is by reading the script of Nyonya-Nyonya by Wisran Hadi, then inventaring the data. Validating data is by performing detail description technic, data analysis technic, inventarizing data, interpretting data, and concluding and then writing the report. Based on the results of the research, it was concluded the following points. First, the materialism of “Nyonya” contained in the script of play Nyonya-Nyonya is “Nyonya” is oriented towards money and inheritance. Second, the impact of the materialism of “Nyonya” in the script of drama Nyonya-Nyonya by Wisran Hadi is the impact to herself and also the impact to her family. Third, Wisran Hadi has shown a today’s moral crisis through the script of Nyonya-Nyonya.